A novel cobalt-free positive electrode material and preparation method thereof

By developing a cobalt-free cathode material, it uses the combination of lithium, nickel, iron, aluminum and modified element M to sinter it in an inert gas atmosphere, and solves the problems of limited cobalt resources and high cost, and achieves low cost and high performance Lithium ion battery positive electrode material.

CN114566633BActive Publication Date: 2025-02-11SINOCHEM INT CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210212960.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-04
Publication Date
2025-02-11
Estimated Expiration
2042-03-04

AI Technical Summary

Technical Problem

The cobalt resources used in the existing lithium-ion battery cathode materials are limited and costly, which leads to the lithium battery industry facing the problems of resource shortage and high costs.

Method used

A cobalt-free cathode material was developed with the chemical formula of LimNixFeyAlzM(1-x-y-z)O2·nB2O3, by combining lithium sources, nickel sources, iron sources, aluminum sources, carbon sources and modified elements M (such as W, Ta, Ti ) Mix and sintering treatment in an inert gas atmosphere.

Benefits of technology

The cobalt-free cathode material has the advantages of low raw material cost, simple preparation process, good repeatability, easy mass production, and relatively friendly to the environment. The discharge platform voltage is higher than that of lithium iron phosphate cathode material, which improves the performance and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003532417790000201
    Figure BDA0003532417790000201
  • Figure BDA0003532417790000211
    Figure BDA0003532417790000211
  • Figure BDA0003532417790000212
    Figure BDA0003532417790000212
Patent Text Reader

Abstract

The present invention provides a novel cobalt-free positive electrode material and a preparation method thereof. The chemical formula of the cobalt-free positive electrode material is Li m Ni x Fe y Al z M (1‑x‑y‑z) O2·nB2O3, wherein M is one or more elements selected from W, Ta, Ti, Si, Mg, Ca, Sr, Ba, Ra, Sc, Y, Zr, Nb, Hf, Cr and Mo, 0.95≤m≤2, 0.05≤x≤0.9, 0.05≤y≤0.9, 0.02≤z≤0.3, 0≤n≤0.005. The cobalt-free positive electrode material of the present invention has the advantages of low raw material cost, simple preparation process, good repeatability, easy mass production, relatively friendly to the environment, etc., and the discharge platform voltage is higher than that of lithium iron phosphate positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery positive electrode materials, and specifically relates to a novel cobalt-free positive electrode material and a preparation method thereof. Background Art

[0002] With the gradual rise of the new energy vehicle market, power lithium-ion batteries have become a strong growth point in the battery industry, and the trend of increasing product demand has become a reality. In the research and development and application of lithium batteries, the positive electrode material is required to have the characteristics of high potential, high specific capacity, high density, etc., and to maintain a long service life and better usage density.

[0003] A key raw material for ternary lithium-ion batteries currently used on a large scale in the field of passenger cars is metal cobalt. However, the global cobalt reserves are limited, with the average mass content of cobalt in the earth's crust being only 0.001%. In addition, the world's cobalt reserves are mainly concentrated in Australia and the perennially unstable African country of Congo. The cobalt resource reserves of these two countries account for about 62.86% of the world's total cobalt reserves. Therefore, low-cost cobalt-free cathode materials have become one of the mainstream trends in the future development of the lithium battery industry. Summary of the invention

[0004] The present invention discloses a cobalt-free positive electrode material and a preparation method thereof. The positive electrode material of the present invention has the advantages of low raw material cost, simple preparation process, good repeatability, easy mass production, relatively friendly to the environment, and a discharge platform voltage higher than that of lithium iron phosphate positive electrode material.

[0005] Specifically, the present invention provides a cobalt-free positive electrode material, the chemical formula of the cobalt-free positive electrode material is Li m Ni x Fe y Al z M (1-x-y-z) O2·nB2O3, wherein M is one or more elements selected from W, Ta, Ti, Si, Mg, Ca, Sr, Ba, Ra, Sc, Y, Zr, Nb, Hf, Cr and Mo, 0.95≤m≤2, 0.05≤x≤0.9, 0.05≤y≤0.9, 0.02≤z≤0.3, and 0≤n≤0.005.

[0006] In one or more embodiments, the M is one or more elements selected from W, Ta, Ti, Mg, Sr, Ba, Y, Zr, Hf, Cr and Mo.

[0007] In one or more embodiments, in the cobalt-free positive electrode material, the mass content of M is 500 ppm-100000 ppm, preferably 1000-50000 ppm.

[0008] In one or more embodiments, the M includes one or two selected from W elements and Ti elements.

[0009] In one or more embodiments, the M comprises W element; preferably, in the cobalt-free positive electrode material, the content of W element is 0.1-2wt%, preferably 0.2-1wt%, and more preferably 0.25-0.5wt%.

[0010] In one or more embodiments, the M comprises Ti element; preferably, in the cobalt-free positive electrode material, the content of W element is 0.1-2wt%, preferably 0.2-1wt%.

[0011] In one or more embodiments, the mass content of B element in the cobalt-free positive electrode material is 500-2000 ppm.

[0012] In one or more embodiments, the cobalt-free cathode material has one or more of the following features:

[0013] 1≤m≤1.5, preferably 1.05≤m≤1.2;

[0014] 0.5≤x≤0.8, preferably 0.6≤x≤0.7;

[0015] 0.1≤y≤0.5, preferably 0.1≤y≤0.2;

[0016] 0.05≤z≤0.2, preferably 0.1≤z≤0.2.

[0017] In one or more embodiments, the cobalt-free positive electrode material is formed by stacking micron-sized single-crystal-like particles, and the micron-sized single-crystal-like particles are formed by agglomerating nano-sized spherical-like particles; preferably, the particle size of the nano-sized spherical-like particles is 200-600nm; preferably, the particle size of the micron-sized single-crystal-like particles is 1-10μm.

[0018] In one or more embodiments, the D50 particle size of the cobalt-free positive electrode material is 1-3 μm.

[0019] In one or more embodiments, the cobalt-free cathode material has a powder tap density of 1-2 g / cc.

[0020] The present invention also provides a method for preparing the cobalt-free positive electrode material according to any embodiment of the present invention, the method comprising the following steps:

[0021] (1) mixing a lithium source, a nickel source, an iron source, an aluminum source, a carbon source and a M source uniformly;

[0022] (2) heat-treating the mixture obtained in step (1) at 750-850° C. in an inert gas atmosphere to obtain a cobalt-free positive electrode material;

[0023] Optionally, the method further comprises:

[0024] (3) After the cobalt-free positive electrode material obtained in step (2) is uniformly mixed with a boron source, heat-insulating treatment is performed at 250-350° C. in an inert gas atmosphere to obtain a cobalt-free positive electrode material containing boron.

[0025] In one or more embodiments, the lithium source is selected from one or both of lithium carbonate and lithium hydroxide.

[0026] In one or more embodiments, the nickel source is selected from one or more of nickel hydroxide, nickel carbonate and nickel sulfate, preferably spherical nickel hydroxide.

[0027] In one or more embodiments, the iron source is selected from one or more of ferrous acetate dihydrate, ferrous sulfate, ferrous carbonate, ferrous chloride and ferric chloride.

[0028] In one or more embodiments, the aluminum source is selected from aluminum oxide and aluminum hydroxide, preferably selected from one or both of lamellar aluminum oxide and lamellar aluminum hydroxide.

[0029] In one or more embodiments, the carbon source is selected from one or more of glucose, sucrose and graphene.

[0030] In one or more embodiments, the carbon source is used in an amount of 2-10% of the total weight of all raw materials.

[0031] In one or more embodiments, the M source includes one or two selected from tungsten trioxide and titanium dioxide; the tungsten trioxide is preferably nano-sized tungsten trioxide, and the titanium dioxide is preferably nano-sized titanium dioxide.

[0032] In one or more embodiments, in step (1), a planetary ball mill is used to mix the materials, the rotation speed of the ball mill is preferably 150-250 r / min, and the ball milling time is preferably 30-60 min.

[0033] In one or more embodiments, in step (2), a tubular atmosphere furnace is used for heat preservation.

[0034] In one or more embodiments, in step (2), the temperature is increased to the holding temperature at a heating rate of 1-3°C / min.

[0035] In one or more embodiments, in step (2), the insulation time is 10-18 hours.

[0036] In one or more embodiments, in step (2), the temperature is lowered to below 100° C. after keeping warm, and the cooling rate is preferably 2-5° C. / min.

[0037] In one or more embodiments, step (2) further comprises grinding and sieving the obtained cobalt-free positive electrode material.

[0038] In one or more embodiments, in step (3), the boron source is boric acid.

[0039] In one or more embodiments, in step (3), a high-speed mixer is used for mixing, and the rotation speed of the high-speed mixer is preferably 1000-3000 r / min, and the mixing time is preferably 10-30 min.

[0040] In one or more embodiments, in step (3), a tubular atmosphere furnace is used for heat preservation.

[0041] In one or more embodiments, in step (3), the temperature is increased to the holding temperature at a heating rate of 1-3°C / min.

[0042] In one or more embodiments, in step (3), the insulation time is 2-6 hours.

[0043] In one or more embodiments, in step (3), the temperature is lowered to below 100° C. after keeping warm, and the cooling is preferably carried out naturally.

[0044] The present invention also provides a cobalt-free positive electrode material prepared by the method described in any embodiment of the present invention.

[0045] The present invention also provides a positive electrode plate, wherein the positive electrode plate comprises the cobalt-free positive electrode material described in any embodiment of the present invention.

[0046] The present invention also provides a lithium-ion battery, which includes the positive electrode sheet described in any embodiment of the present invention.

[0047] The present invention also provides a lithium-ion battery cell, wherein the lithium-ion battery cell comprises the positive electrode sheet described in any embodiment of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a scanning electron microscope photograph (5k times) of the positive electrode material of Example 1.

[0049] Figure 2 This is a scanning electron microscope photograph (20k times) of the positive electrode material of Example 1.

[0050] Figure 3 This is a scanning electron microscope photograph (2k times) of the positive electrode material of Example 2.

[0051] Figure 4 This is a scanning electron microscope photograph (20k times) of the positive electrode material of Example 2.

[0052] Figure 5 This is a scanning electron microscope photograph (2k times) of the positive electrode material of Example 3.

[0053] Figure 6 This is a scanning electron microscope photograph (20k times) of the positive electrode material of Example 3.

[0054] Figure 7 This is a scanning electron microscope photograph (2k times) of the positive electrode material of Example 4.

[0055] Figure 8 This is a scanning electron microscope photograph (20k times) of the positive electrode material of Example 4.

[0056] Fig. 9 This is the first cycle charge and discharge curve of the positive electrode material of Example 1.

[0057] Fig.10 This is a 50-cycle capacity retention curve of the positive electrode material 1CC / 1DC of Example 1. DETAILED DESCRIPTION

[0058] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0059] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0060] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0061] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0062] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0063] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0064] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0065] Cobalt-free cathode material

[0066] The positive electrode material of the present invention is Li-ion modified with Ni, Fe, Al as main elements and certain specific elements M (such as W, Ta, Ti, Si, Mg, Ca, Sr, Ba, Ra, Sc, Y, Zr, Nb, Hf, Cr, Mo, etc.) m Ni x Fe y Al z M (1-x-y-z) O2 cobalt-free positive electrode material, wherein 0.95≤m≤2, 0.05≤x≤0.90, 0.05≤y≤0.90, 0.02≤z≤0.30. M is preferably W, Ta, Ti, Mg, Sr, Ba, Y, Zr, Hf, Cr, Mo, etc. M can exist in a doped form or in a coated form. In the positive electrode material, the mass content of M is between 500ppm-100000ppm, preferably between 1000-50000ppm. At this content, the positive electrode material has the advantages of good uniformity of particle morphology, moderate particle size, high gram capacity and high cycle stability. In the positive electrode material of the present invention, Ni and Fe are variable valence elements. As charging proceeds, Ni 2+ To high valence Ni 3+ And Ni 4+ Transformation, Fe 2+ Fe 3+ Ni and Fe are the elements that contribute to the capacity, while Al and the modifying element M do not participate in the valence change, and mainly play the role of stabilizing the structure, improving the rate and enhancing the thermal stability.

[0067] The present invention finds that adding a modifying element M, such as tungsten or titanium, to the positive electrode material of the present invention can improve the initial charge and discharge performance of the battery, including the initial charge specific capacity, the initial discharge specific capacity, and the initial efficiency, increase the discharge platform voltage and the cycle capacity retention rate, and enhance the rate performance, wherein the effect of using tungsten modification is better than that of titanium modification, and tungsten modification can also improve the low-temperature performance.

[0068] In the positive electrode material of the present invention, the mass content of the modifying element M is 500 ppm-100000 ppm, for example, 1000 ppm, 2000 ppm, 5000 ppm, 10000 ppm, 20000 ppm, 50000 ppm.

[0069] In the embodiment where the modifying element M includes tungsten, the content of tungsten can be 0.1-2wt%, preferably 0.2-1wt%, such as 0.25wt%, 0.3wt%, 0.33wt%, 0.35wt%, 0.4wt%, 0.5wt%, 0.8wt%, 0.9wt%, 0.95wt%, 0.98wt%. In order to maintain good initial charge and discharge performance and low temperature performance, the content of tungsten is preferably 0.25-0.5wt%.

[0070] In an embodiment where the modifying element M includes titanium, the content of titanium can be 0.1-2wt%, preferably 0.2-1wt%, for example 0.25wt%, 0.3wt%, 0.33wt%, 0.35wt%, 0.4wt%, 0.5wt%, 0.8wt%, 0.9wt%, 0.95wt%, 0.98wt%.

[0071] In some embodiments, the chemical formula of the positive electrode material of the present invention is Li m Ni x Fe y Al z M (1-x-y-z) In O2·nB2O3, 1≤m≤1.5, preferably 1.05≤m≤1.2, for example, m can be 1.08, 1.1, 1.12, 1.15; 0.5≤x≤0.8, preferably 0.6≤x≤0.7, for example, x can be 0.65, 2 / 3, 0.68; 0.1≤y≤0.5, preferably 0.1≤y≤0.2, for example, y can be 0.15, 1 / 6, 0.18; 0.05≤z≤0.2, preferably 0.1≤z≤0.2, for example, z can be 0.15, 0.1617, 0.165, 0.18. This is conducive to improving the performance of the battery. In the present invention, x+y+z<1.

[0072] The positive electrode material of the present invention has a moderate D50 size (about 1-3 μm) and a high powder tap density (1-2 g / cc), which is conducive to improving battery performance. For example, the D50 particle size of the positive electrode material of the present invention can be 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.5 μm, 3 μm. The powder tap density of the positive electrode material of the present invention can be 1 g / cc, 1.2 g / cc, 1.4 g / cc, 1.6 g / cc, 1.8 g / cc, 2 g / cc. In the present invention, the test method of the powder tap density is: 20 g of the positive electrode material sample is placed in a measuring cylinder and tested using a tap density meter, wherein the vibration is 3000 times and the frequency is 250 times / min.

[0073] In the present invention, the test method of particle size D50 is as follows: take a small amount of positive electrode material powder sample in a 100mL beaker, add 40mL of water, and perform external ultrasound at 240W for 15s, and pour all of it into the laser particle size analyzer sampling system for full dispersion so that the shading degree is 8-15%, and the internal ultrasound (about 20W) is always turned on, and the refractive index is 2.90, so as to perform the D50 test of the positive electrode material powder sample.

[0074] The positive electrode material of the present invention is formed by stacking micron-sized single-crystal particles, wherein the micron-sized single-crystal particles are formed by agglomerating nano-sized spherical particles. The particle size of the nano-sized spherical particles is preferably 200-600nm, such as 300nm, 400nm, 500nm. The particle size of the micron-sized single-crystal particles is preferably 1-10μm, such as 2μm, 4μm, 6μm, 8μm, 9μm. This is conducive to improving battery performance.

[0075] The positive electrode material of the present invention may optionally or preferably be modified by containing boron element, for example, the positive electrode material of the above chemical formula may be Li m Ni x Fe y Al z M (1-x-y-z) O2 is doped or coated with boron oxide to obtain a positive electrode material with the chemical formula Li m Ni x Fe y Al z M (1-x-y-z) O2·nB2O3 positive electrode materials can further improve the gram capacity of positive electrode active materials, improve the initial charge and discharge performance, cycle performance, rate performance and low temperature performance. In some performances, M and B also have a synergistic effect, for example, Ti and B have a synergistic effect in improving the rate charge capacity retention rate.

[0076] The boron-modified positive electrode material Li m Ni x Fe y Alz M (1-x-y-z) In O2·nB2O3, m, x, y, z are as described above, 0≤n≤0.005, for example, n can be 0.001, 0.002, 0.003, 0.004. This is beneficial to improving the performance of the battery. In a preferred embodiment, the mass content of the B element in the positive electrode material is 500-2000ppm, for example, 800ppm, 1000ppm, 1200ppm, 1500ppm.

[0077] The positive electrode material of the present invention does not contain cobalt element, and is obtained by uniformly mixing lithium source, nickel source, iron source, aluminum source, carbon source and M source and then subjecting the mixture to heat preservation treatment (sintering) in an inert gas atmosphere.

[0078] In the raw materials of the positive electrode material of the present invention, the lithium source may be lithium carbonate (Li2CO3), lithium hydroxide (LiOH·H2O), etc. In some embodiments, the lithium source is lithium carbonate.

[0079] In the raw materials of the positive electrode material of the present invention, the nickel source can be nickel hydroxide (Ni(OH)2), nickel carbonate (NiCO3), nickel sulfate (NiSO4), etc. The nickel source is preferably spherical. In some embodiments, the nickel source is spherical nickel hydroxide.

[0080] In the raw materials of the positive electrode material of the present invention, the iron source can be a divalent iron compound, a trivalent iron compound or a mixture thereof, for example, the iron source can be ferrous acetate dihydrate (C4H6FeO4·2H2O), ferrous sulfate (FeSO4), ferrous carbonate (FeCO3), ferrous chloride (FeCl2), ferric chloride (FeCl3), etc. In some embodiments, the iron source is ferrous acetate dihydrate.

[0081] In the raw materials of the positive electrode material of the present invention, the aluminum source can be aluminum oxide, aluminum hydroxide, etc. The aluminum source is preferably in a lamellar form. In some embodiments, the aluminum source is lamellar aluminum oxide.

[0082] In the raw materials of the cathode material of the present invention, the carbon source may be glucose, sucrose, graphene, etc. In some embodiments, the carbon source is glucose.

[0083] In the present invention, the M source may be an oxide, hydroxide, carbonate, etc. of the M element. The M source is preferably nanometer-sized. In some embodiments, M is one or both selected from tungsten and titanium. In the raw material of the positive electrode material of the present invention, the tungsten source may be tungsten trioxide, preferably nano tungsten trioxide. In the raw material of the positive electrode material of the present invention, the titanium source may be titanium dioxide, preferably nano titanium dioxide.

[0084] Each raw material is prepared according to the target element composition of the positive electrode material, mixed evenly and then sintered. Preferably, the raw materials are ball-milled before sintering until the mixed powder material is visually uniform in color and there is no granularity after grinding. The speed of the ball mill is preferably 150-250r / min, for example, 200r / min, and the ball milling time is preferably 30-60min, which is conducive to sintering and improving material properties. Sintering can be carried out in a tubular furnace. During sintering, an inert gas, such as nitrogen, is used for protection. The sintering temperature can be 750-850°C, for example, 780°C, 800°C, 810°C, 820°C, 830°C, 840°C. The performance of the positive electrode material can be adjusted by regulating the sintering temperature. At a higher sintering temperature, the battery's first effect, cycle performance and low-temperature performance are better. Therefore, it is preferred to sinter at 800-850°C. At this temperature, the lithium salt is fully melted and the solid-phase sintering reaction with the raw material is more complete. The resulting positive electrode material has a more rounded morphology and has better bonding between the substrate and the coating agent during coating and secondary sintering. The heating rate can be 1-3°C / min, such as 1.5°C / min, 2°C / min, and 2.5°C / min, to the sintering temperature. The sintering time can be 10-18h, such as 12h, 14h, and 16h. After sintering, the temperature is lowered to below 100°C, and the cooling rate is preferably 2-5°C / min, such as 3°C / min and 4°C / min. The positive electrode material can be post-treated. The post-treatment can be selected from grinding, screening, and drying.

[0085] When preparing the positive electrode material modified by boron oxide, the positive electrode material obtained by the above sintering is further mixed with the boron source and then heat-insulated (sintered) in an inert gas. The boron source can be boric acid. A high-speed mixer can be used to mix the positive electrode material and the boron source. The speed of the high-speed mixer is preferably 1000-3000r / min, for example, 2000r / min. The mixing time is preferably 10-30min, for example, 15min. In this step of sintering, sintering can be carried out in a tubular furnace. During sintering, an inert gas, such as nitrogen, is used for protection. The sintering temperature can be 250-350°C, for example, 280°C, 290°C, 300°C, 310°C, 320°C. The heating rate can be 1-3°C / min, for example, 1.5°C / min, 2°C / min, 2.5°C / min, to the sintering temperature. The sintering time can be 2-6h, for example, 3h, 4h, 5h. After sintering, the temperature is lowered to below 100° C., which may be a natural cooling process. The boron oxide-modified positive electrode material may be post-treated, such as being dried.

[0086] Positive electrode and lithium-ion battery

[0087] The present invention provides a positive electrode sheet containing the positive electrode material described in any embodiment of the present invention, a lithium-ion battery cell containing the positive electrode sheet, and a lithium-ion battery containing the positive electrode sheet.

[0088] A lithium-ion battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet, the negative electrode sheet and the separator are stacked (for example, in a zigzag stack or in a winding stack) according to design requirements to obtain a lithium-ion battery cell.

[0089] The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer formed on the surface of the positive electrode current collector. The positive electrode material layer includes a positive electrode material, a conductive agent and a binder. The positive electrode material layer is usually coated on the positive electrode current collector by a positive electrode slurry containing a positive electrode material, a conductive agent, a binder and a solvent, and then obtained by rolling, die cutting and baking. The solvent of the positive electrode slurry can be N-methylpyrrolidone (NMP). The positive electrode current collector can be copper foil, aluminum foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The positive electrode material can be selected from lithium iron phosphate, binary positive electrode material, ternary positive electrode material, quaternary positive electrode material, etc. Preferably, the positive electrode material is a cobalt-free positive electrode material described in any embodiment of the present invention. The conductive agent of the positive electrode can be one or more selected from conductive carbon black (SP), carbon fiber (CF), acetylene black, conductive graphite, graphene, carbon nanotubes and carbon microspheres. Examples of conductive carbon black include super carbon black (super-c65). The binder of the positive electrode can be one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyvinyl alcohol, polyolefin, styrene-butadiene rubber, fluorinated rubber, polyurethane and sodium alginate. In some embodiments, the conductive agent in the positive electrode material layer is SP and the binder is PVDF. The content ratio of each component in the positive electrode material layer can be conventional, for example, the mass fraction of the positive electrode active material can be 80%-98%, such as 84%, 88%, 92%, 96%, the mass fraction of the conductive agent can be 1%-10%, such as 2%, 4%, 6%, 8%, and the mass fraction of the binder can be 1%-10%, such as 2%, 4%, 6%, 8%.

[0090] The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector. The negative electrode current collector may be a copper foil. The negative electrode material layer includes a negative electrode material, a conductive agent, and a binder. The negative electrode material layer is obtained by coating a negative electrode slurry containing a negative electrode material onto a positive electrode current collector, and then rolling, die cutting, and baking. The solvent of the negative electrode slurry may be water. The negative electrode material may be selected from graphite, lithium metal, lithium alloy, and the like. In some embodiments, the negative electrode material is graphite.

[0091] The diaphragm can be a polymer diaphragm, a ceramic diaphragm or a polymer / ceramic composite diaphragm. The polymer diaphragm includes a single-layer polymer diaphragm and a multi-layer polymer diaphragm. In some embodiments, the diaphragm is a polypropylene (PP) diaphragm.

[0092] After obtaining the battery cell, the battery cell is encapsulated in a shell, and after drying, liquid injection (injection of electrolyte), packaging, standing, forming, and shaping, a lithium-ion battery can be obtained.

[0093] Lithium-ion battery electrolytes include organic solvents and lithium salts. Organic solvents commonly used in electrolytes are carbonate solvents. Suitable carbonate solvents include, but are not limited to, one or more selected from ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, γ-butyrolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), preferably two or more. Preferably, the carbonate solvent includes at least one cyclic carbonate and at least one chain carbonate. Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, butylene carbonate, and γ-butyrolactone. Examples of chain carbonates include dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The mass ratio of cyclic carbonates to chain carbonates can be 1:4 to 1:1. For example, 1:3, 3:7, 1:2. In some embodiments, the organic solvent includes cyclic carbonate EC and chain carbonate EMC. The lithium salt in the electrolyte of the present invention can be a lithium salt commonly used in the art, including but not limited to lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium bis(fluorosulfonyl) imide (LiFSI), lithium bisoxalate borate (LiBOB), lithium difluorooxalate borate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium fluoride (LiF), lithium trifluoromethanesulfonate (LiCF3SO3), etc. In some embodiments, the lithium salt is LiPF6. The concentration of the lithium salt in the electrolyte can be 0.5-2mol / L, for example 0.8mol / L, 1mol / L, 1.2mol / L.

[0094] The present invention has the following beneficial effects:

[0095] The positive electrode material of the present invention has the advantages of low raw material cost, simple preparation process, good repeatability, easy mass production, and relatively friendly to the environment, and the discharge platform voltage (about 3.57V) is higher than that of lithium iron phosphate positive electrode material, and the discharge platform voltage of lithium iron phosphate is generally 3.2V. The positive electrode material of the present invention has a moderate D50 size (about 1-3μm) and a high powder tap density (1-2g / cc). The positive electrode material of the present invention can give the battery improved initial charge and discharge performance, cycle capacity retention rate and rate performance. In some preferred embodiments, the positive electrode material of the present invention can give the battery relatively excellent low temperature performance. The present invention also provides a preparation method for the positive electrode material of the present invention using a solid phase sintering method. Compared with other materials, the positive electrode material of the present invention has the cost advantage of a simple synthesis process and lower process conditions required for mass production.

[0096] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0097] Example 1

[0098] This embodiment provides a new positive electrode material, and the preparation, characterization and performance testing methods are as follows:

[0099] (1) According to the molar ratio of nickel, iron, aluminum and tungsten elements being 400:100:99:1, 61.795 g of spherical nickel hydroxide (Ni(OH)2), 34.974 g of ferrous acetate dihydrate (C4H6FeO4·2H2O), 8.412 g of lamellar aluminum oxide (Al2O3), 0.3864 g of nano-scale tungsten trioxide (WO3) (the mass fraction of W in the final positive electrode material is 3300 ppm) and 40.635 g of lithium carbonate (Li2CO3) were weighed respectively; 7.695 g of glucose with a mass fraction of 5% was weighed (based on the sum of all raw materials);

[0100] (2) Place the weighed raw materials in a ball mill, and use a planetary ball mill at 200 r / min for 30-60 min. When the mixed powder material is visually uniform in color and has no graininess, stop the ball milling;

[0101] (3) The mixed powder material is transferred into a sagger, spread evenly, and placed in a tubular atmosphere furnace. In a N2 atmosphere, the temperature is raised to 820°C at 2°C / min, kept at this temperature for 14 hours, and then cooled to 100°C at 4°C / min before being taken out;

[0102] (4) performing ultracentrifugal grinding and screening on the positive electrode material cooled to room temperature;

[0103] (5) In order to further increase the gram capacity of the positive electrode active material and improve the cycle and low-temperature performance, the obtained positive electrode material was mechanically stirred and mixed with 1000 ppm (accounting for the total mass of the positive electrode material, calculated according to the mass of the boron element) of boric acid, and then placed in a high-speed mixer at 2000 r / min for 15 min. Then, it was placed in a tubular atmosphere furnace and heated to 300°C at 2°C / min under a N2 atmosphere. After being kept warm for 4 h, it was naturally cooled to 100°C and taken out to finally obtain boron oxide-modified Li 1.1 Ni 2 / 3 Fe 1 / 6Al 0.165 W 0.00167O2 positive electrode material; place the prepared positive electrode material in a vacuum drying oven at 100°C for 4 hours, take it out, weigh an appropriate amount of powder and stick it on the sample table, and place it in the sample chamber of the instrument, and perform surface micromorphology tests at different magnifications under high vacuum conditions; weigh 20.00g of the prepared positive electrode material sample, place it in a measuring cylinder, and use a tap density meter to test the tap density, wherein the vibration is 3000 times, and the frequency is 250 times / min;

[0104] (6) The prepared positive electrode material, conductive agent super carbon black (super-c65), binder (PVDF glue with a solid content of 6.25%) and NMP solvent were homogenized and coated to prepare a positive electrode sheet, wherein the mass fraction of the positive electrode material was 92%, the mass fraction of the conductive agent super carbon black (super-c65) and the mass fraction of the binder were 4% each; graphite was used as the negative electrode, PP separator was used, the electrolyte lithium salt was 1 mol / L LiPF6, and the solvent was EC and EMC with a mass ratio of 3:7, and assembled into a 2Ah soft pack battery;

[0105] (7) Using the blue battery test system, the voltage range is 2.75-4.25V, the first charge and discharge test is carried out under 0.1C charge and 0.1C discharge. After two weeks of cycle, it is changed to 1C charge and 1C discharge. After 50 cycles, the charge and discharge cycle is carried out under 0.1C charge and 0.1C discharge for two weeks. The data is shown in Table 2;

[0106] (8) The blue battery test system was used with a voltage range of 2.75-4.25 V to conduct 0.33C / 0.5C / 1C / 2C rate charging and 0.33C / 0.5C / 1C / 2C / 3C rate discharging tests, and 25℃ / 55℃ / 10℃ / 0℃ / -10℃ / -20℃ high and low temperature performance tests. The data are shown in Table 3.

[0107] Example 2

[0108] This embodiment provides a new positive electrode material, and the preparation, characterization and performance testing methods are as follows:

[0109] (1) According to the molar ratio of nickel, iron, aluminum and tungsten elements being 400:100:99:1, 61.795 g of spherical nickel hydroxide (Ni(OH)2), 34.974 g of ferrous acetate dihydrate (C4H6FeO4·2H2O), 8.412 g of lamellar aluminum oxide (Al2O3), 0.3864 g of nano-scale tungsten trioxide (WO3) (the mass fraction of W in the final positive electrode material is 3300 ppm) and 40.635 g of lithium carbonate (Li2CO3) were weighed respectively; 7.695 g of glucose with a mass fraction of 5% was weighed (based on the sum of all raw materials);

[0110] (2) Place the weighed raw materials in a ball mill, and use a planetary ball mill at 200 r / min for 30-60 min. When the mixed powder material is visually uniform in color and has no graininess, stop the ball milling;

[0111] (3) The mixed powder material is transferred into a sagger, spread evenly, and placed in a tubular atmosphere furnace. In a N2 atmosphere, the temperature is raised to 780°C at 2°C / min, kept at this temperature for 14 hours, and then cooled to 100°C at 4°C / min before being taken out;

[0112] (4) performing ultracentrifugal grinding and screening on the positive electrode material cooled to room temperature;

[0113] (5) In order to further increase the gram capacity of the positive electrode active material and improve the cycle and low-temperature performance, the obtained positive electrode material was mechanically stirred and mixed with 1000 ppm (accounting for the total mass of the positive electrode material, calculated according to the mass of the boron element) of boric acid, and then placed in a high-speed mixer at 2000 r / min for 15 min. Then, it was placed in a tubular atmosphere furnace and heated to 300°C at 2°C / min under a N2 atmosphere. After being kept warm for 4 h, it was naturally cooled to 100°C and taken out to finally obtain boron oxide-modified Li 1.1 Ni 2 / 3 Fe 1 / 6Al 0.165 W 0.00167 O2 cobalt-free positive electrode material; place the prepared positive electrode material in a vacuum drying oven at 100°C and dry for 4 hours, take out and weigh an appropriate amount of powder and stick it on the sample table, and place it in the sample chamber of the instrument, and perform surface micromorphology tests at different magnifications under high vacuum conditions; weigh 20.00g of the prepared positive electrode material sample, place it in a measuring cylinder, and use a tap density meter to test the tap density, wherein the vibration is 3000 times, and the frequency is 250 times / min;

[0114] (6) The prepared positive electrode material, conductive agent super carbon black (super-c65), binder (PVDF glue with a solid content of 6.25%) and NMP solvent were homogenized and coated to prepare a positive electrode sheet, wherein the mass fraction of the positive electrode material was 92%, the mass fraction of the conductive agent super carbon black (super-c65) and the mass fraction of the binder were 4% each; graphite was used as the negative electrode, PP separator was used, the electrolyte lithium salt was 1 mol / L LiPF6, and the solvent was EC and EMC with a mass ratio of 3:7, and assembled into a 2Ah soft pack battery;

[0115] (7) Using the blue battery test system, the voltage range is 2.75-4.25V, the first charge and discharge test is carried out under 0.1C charge and 0.1C discharge. After two weeks of cycle, it is changed to 1C charge and 1C discharge. After 50 cycles, the charge and discharge cycle is carried out under 0.1C charge and 0.1C discharge for two weeks. The data is shown in Table 2;

[0116] (8) The blue battery test system was used with a voltage range of 2.75-4.25 V to conduct 0.33C / 0.5C / 1C / 2C rate charging and 0.33C / 0.5C / 1C / 2C / 3C rate discharging tests, and 25℃ / 55℃ / 10℃ / 0℃ / -10℃ / -20℃ high and low temperature performance tests. The data are shown in Table 3.

[0117] Example 3

[0118] This embodiment provides a new positive electrode material, and the preparation, characterization and performance testing methods are as follows:

[0119] (1) According to the molar ratio of nickel, iron, aluminum and tungsten elements of 400:100:97:3, 61.795 g of spherical nickel hydroxide (Ni(OH)2), 34.974 g of ferrous acetate dihydrate (C4H6FeO4·2H2O), 8.242 g of lamellar aluminum oxide (Al2O3), 1.159 g of nano-scale tungsten trioxide (WO3) (the mass fraction of W in the final positive electrode material is 9800 ppm) and 40.635 g of lithium carbonate (Li2CO3) were weighed respectively; 7.727 g of glucose with a mass fraction of 5% was weighed (based on the sum of all raw materials);

[0120] (2) Place the weighed raw materials in a ball mill, and use a planetary ball mill at 200 r / min for 30-60 min. When the mixed powder material is visually uniform in color and has no graininess, stop the ball milling;

[0121] (3) The mixed powder material is transferred into a sagger, spread evenly, and placed in a tubular atmosphere furnace. In a N2 atmosphere, the temperature is raised to 820°C at 2°C / min, kept at this temperature for 14 hours, and then cooled to 100°C at 4°C / min before being taken out;

[0122] (4) performing ultracentrifugal grinding and screening on the positive electrode material cooled to room temperature;

[0123] (5) In order to further increase the gram capacity of the positive electrode active material and improve the cycle and low-temperature performance, the obtained positive electrode material was mechanically stirred and mixed with 1000 ppm (accounting for the total mass of the positive electrode material, calculated according to the mass of the boron element) of boric acid, and then placed in a high-speed mixer at 2000 r / min for 15 min. Then, it was placed in a tubular atmosphere furnace and heated to 300°C at 2°C / min under a N2 atmosphere. After being kept warm for 4 h, it was naturally cooled to 100°C and taken out to finally obtain boron oxide-modified Li 1.1 Ni 2 / 3 Fe 1 / 6Al 0.1617 W 0.005O2 cobalt-free positive electrode material; place the prepared positive electrode material in a vacuum drying oven at 100°C and dry for 4 hours, take out and weigh an appropriate amount of powder and stick it on the sample table, and place it in the sample chamber of the instrument, and perform surface micromorphology tests at different magnifications under high vacuum conditions; weigh 20.00g of the prepared positive electrode material sample, place it in a measuring cylinder, and use a tap density meter to test the tap density, wherein the vibration is 3000 times, and the frequency is 250 times / min;

[0124] (6) The prepared positive electrode material, conductive agent super carbon black (super-c65), binder (PVDF glue with a solid content of 6.25%) and NMP solvent were homogenized and coated to prepare a positive electrode sheet, wherein the mass fraction of the positive electrode material was 92%, the mass fraction of the conductive agent super carbon black (super-c65) and the mass fraction of the binder were 4% each; graphite was used as the negative electrode, PP separator was used, the electrolyte lithium salt was 1 mol / L LiPF6, and the solvent was EC and EMC with a mass ratio of 3:7, and assembled into a 2Ah soft pack battery;

[0125] (7) Using the blue battery test system, the voltage range is 2.75-4.25V, the first charge and discharge test is carried out under 0.1C charge and 0.1C discharge. After two weeks of cycle, it is changed to 1C charge and 1C discharge. After 50 cycles, the charge and discharge cycle is carried out under 0.1C charge and 0.1C discharge for two weeks. The data is shown in Table 2;

[0126] (8) The blue battery test system was used with a voltage range of 2.75-4.25 V to conduct 0.33C / 0.5C / 1C / 2C rate charging and 0.33C / 0.5C / 1C / 2C / 3C rate discharging tests, and 25℃ / 55℃ / 10℃ / 0℃ / -10℃ / -20℃ high and low temperature performance tests. The data are shown in Table 3.

[0127] Example 4

[0128] This embodiment provides a new positive electrode material, and the preparation, characterization and performance testing methods are as follows:

[0129] (1) According to the molar ratio of nickel, iron, aluminum and titanium elements being 400:100:99:1, 61.795 g of spherical nickel hydroxide (Ni(OH)2), 34.974 g of ferrous acetate dihydrate (C4H6FeO4·2H2O), 8.412 g of lamellar aluminum oxide (Al2O3), 0.133 g of nano-scale titanium dioxide (TiO2) (the mass fraction of Ti in the final positive electrode material is 900 ppm) and 40.635 g of lithium carbonate (Li2CO3) were weighed respectively; 7.682 g of glucose with a mass fraction of 5% was weighed (based on the sum of all raw materials);

[0130] (2) Place the weighed raw materials in a ball mill, and use a planetary ball mill at 200 r / min for 30-60 min. When the mixed powder material is visually uniform in color and has no graininess, stop the ball milling;

[0131] (3) The mixed powder material is transferred into a sagger, spread evenly, and placed in a tubular atmosphere furnace. In a N2 atmosphere, the temperature is raised to 820°C at 2°C / min, kept at this temperature for 14 hours, and then cooled to 100°C at 4°C / min before being taken out;

[0132] (4) performing ultracentrifugal grinding and screening on the positive electrode material cooled to room temperature;

[0133] (5) In order to further increase the gram capacity of the positive electrode active material and improve the cycle and low-temperature performance, the obtained positive electrode material was mechanically stirred and mixed with 1000 ppm (accounting for the total mass of the positive electrode material, calculated according to the mass of the boron element) of boric acid, and then placed in a high-speed mixer at 2000 r / min for 15 min. Then, it was placed in a tubular atmosphere furnace and heated to 300°C at 2°C / min under a N2 atmosphere. After being kept warm for 4 h, it was naturally cooled to 100°C and taken out to finally obtain boron oxide-modified Li 1.1 Ni 2 / 3 Fe 1 / 6Al 0.165 Ti 0.00167 O2 cobalt-free positive electrode material; place the prepared positive electrode material in a vacuum drying oven at 100°C and dry for 4 hours, take out and weigh an appropriate amount of powder and stick it on the sample table, and place it in the sample chamber of the instrument, and perform surface micromorphology tests at different magnifications under high vacuum conditions; weigh 20.00g of the prepared positive electrode material sample, place it in a measuring cylinder, and use a tap density meter to test the tap density, wherein the vibration is 3000 times, and the frequency is 250 times / min;

[0134] (6) The prepared positive electrode material, conductive agent super carbon black (super-c65), binder (PVDF glue with a solid content of 6.25%) and NMP solvent were homogenized and coated to prepare a positive electrode sheet, wherein the mass fraction of the positive electrode material was 92%, the mass fraction of the conductive agent super carbon black (super-c65) and the mass fraction of the binder were 4% each; graphite was used as the negative electrode, PP separator was used, the electrolyte lithium salt was 1 mol / L LiPF6, and the solvent was EC and EMC with a mass ratio of 3:7, and assembled into a 2Ah soft pack battery;

[0135] (7) Using the blue battery test system, the voltage range is 2.75-4.25V, the first charge and discharge test is carried out under 0.1C charge and 0.1C discharge. After two weeks of cycle, it is changed to 1C charge and 1C discharge. After 50 cycles, the charge and discharge cycle is carried out under 0.1C charge and 0.1C discharge for two weeks. The data is shown in Table 2;

[0136] (8) The blue battery test system was used with a voltage range of 2.75-4.25 V to conduct 0.33C / 0.5C / 1C / 2C rate charging and 0.33C / 0.5C / 1C / 2C / 3C rate discharging tests, and 25℃ / 55℃ / 10℃ / 0℃ / -10℃ / -20℃ high and low temperature performance tests. The data are shown in Table 3.

[0137] Example 5

[0138] This embodiment provides a new positive electrode material, and the preparation, characterization and performance testing methods are as follows:

[0139] (1) According to the molar ratio of nickel, iron, aluminum and titanium elements being 400:100:99:1, 61.795 g of spherical nickel hydroxide (Ni(OH)2), 34.974 g of ferrous acetate dihydrate (C4H6FeO4·2H2O), 8.412 g of lamellar aluminum oxide (Al2O3), 0.133 g of nano-scale titanium dioxide (TiO2) (the mass fraction of Ti in the final positive electrode material is 900 ppm) and 40.635 g of lithium carbonate (Li2CO3) were weighed respectively; 7.682 g of glucose with a mass fraction of 5% was weighed (based on the sum of all raw materials);

[0140] (2) Place the weighed raw materials in a ball mill, and use a planetary ball mill at 200 r / min for 30-60 min. When the mixed powder material is visually uniform in color and has no graininess, stop the ball milling;

[0141] (3) The mixed powder material is transferred into a sagger, spread evenly, and placed in a tubular atmosphere furnace. In a N2 atmosphere, the temperature is raised to 820°C at 2°C / min, kept at this temperature for 14 hours, and then cooled to 100°C at 4°C / min before being taken out;

[0142] (4) Ultracentrifugal grinding and screening of the cathode material cooled to room temperature are performed to obtain Li 1.1 Ni 2 / 3 Fe 1 / 6Al 0.165 Ti 0.00167O2 cobalt-free positive electrode material; place the prepared positive electrode material in a vacuum drying oven at 100°C and dry for 4 hours, take out and weigh an appropriate amount of powder and stick it on the sample table, and place it in the sample chamber of the instrument, and perform surface micromorphology tests at different magnifications under high vacuum conditions; weigh 20.00g of the prepared positive electrode material sample, place it in a measuring cylinder, and use a tap density meter to test the tap density, wherein the vibration is 3000 times, and the frequency is 250 times / min;

[0143] (5) The prepared positive electrode material, conductive agent super carbon black (super-c65), binder (PVDF glue with a solid content of 6.25%) and NMP solvent were homogenized and coated to prepare a positive electrode sheet, wherein the mass fraction of the positive electrode material was 92%, the mass fractions of the conductive agent super carbon black (super-c65) and the binder were 4% each; graphite was used as the negative electrode, PP diaphragm was used, the electrolyte lithium salt was 1 mol / L LiPF6, and the solvent was EC and EMC with a mass ratio of 3:7, and assembled into a 2Ah soft-pack battery;

[0144] (6) Using the blue battery test system, the voltage range is 2.75-4.25V, the first charge and discharge test is carried out under 0.1C charge and 0.1C discharge. After two weeks of cycle, it is changed to 1C charge and 1C discharge. After 50 cycles, the charge and discharge cycle is carried out under 0.1C charge and 0.1C discharge for two weeks. The data is shown in Table 2;

[0145] (7) The blue battery test system was used with a voltage range of 2.75-4.25 V to conduct 0.33C / 0.5C / 1C / 2C rate charging and 0.33C / 0.5C / 1C / 2C / 3C rate discharging tests, and 25℃ / 55℃ / 10℃ / 0℃ / -10℃ / -20℃ high and low temperature performance tests. The data are shown in Table 3.

[0146] Comparative Example 1

[0147] This comparative example provides a positive electrode material, and the preparation, characterization and performance testing methods are as follows:

[0148] (1) According to the molar ratio of nickel, iron and aluminum being 4:1:1, 61.795 g of spherical nickel hydroxide (Ni(OH)2), 34.974 g of ferrous acetate dihydrate (C4H6FeO4·2H2O), 8.497 g of lamellar aluminum oxide (Al2O3) and 40.635 g of lithium carbonate (Li2CO3) were weighed respectively; 7.679 g of glucose with a mass fraction of 5% was weighed (based on the sum of all raw materials);

[0149] (2) Place the weighed raw materials in a ball mill and use a planetary ball mill at 200 r / min for 30-60 min. Visually inspect the mixed powder material to see that the color is uniform and there is no graininess when grinding. Stop the ball milling and mixing.

[0150] (3) The mixed powder material is transferred into a sagger, spread evenly, and placed in a tubular atmosphere furnace. In a N2 atmosphere, the temperature is raised to 820°C at 2°C / min, kept at this temperature for 14 hours, and then cooled to 100°C at 4°C / min before being taken out;

[0151] (4) performing ultracentrifugal grinding and screening on the positive electrode material cooled to room temperature;

[0152] (5) In order to further increase the gram capacity of the positive electrode active material and improve the cycle and low-temperature performance, the obtained positive electrode material was mechanically stirred and mixed with 1000 ppm (accounting for the total mass of the positive electrode material, calculated according to the mass of the boron element) of boric acid, and then placed in a high-speed mixer at 2000 r / min for 15 min. Then, it was placed in a tubular atmosphere furnace and heated to 300°C at 2°C / min under a N2 atmosphere. After being kept warm for 4 h, it was naturally cooled to 100°C and taken out to finally obtain boron oxide-modified Li 1.1 Ni 2 / 3 Fe 1 / 6 Al 1 / 6O2 cobalt-free positive electrode material; weigh 20.00g of the prepared positive electrode material sample, place it in a measuring cylinder, and use a tap density meter to test the tap density, wherein the vibration is 3000 times, and the frequency is 250 times / min;

[0153] (6) The prepared positive electrode material, conductive agent super carbon black (super-c65), binder (PVDF glue with a solid content of 6.25%) and NMP solvent were homogenized and coated to prepare a positive electrode sheet, wherein the mass fraction of the positive electrode material was 92%, the mass fractions of the conductive agent super carbon black (super-c65) and the binder were 4% each; graphite was used as the negative electrode, PP separator was used, the electrolyte lithium salt was 1 mol / L LiPF6, and the solvent was EC+EMC with a mass ratio of 3:7, and assembled into a 2Ah soft-pack battery;

[0154] (7) Using the blue battery test system, the voltage range is 2.75-4.25V, the first charge and discharge test is carried out under 0.1C charge and 0.1C discharge. After two weeks of cycle, it is changed to 1C charge and 1C discharge. After 50 cycles, the charge and discharge cycle is carried out under 0.1C charge and 0.1C discharge for two weeks. The data is shown in Table 2;

[0155] (8) The blue battery test system was used with a voltage range of 2.75-4.25 V to conduct 0.33C / 0.5C / 1C / 2C rate charging and 0.33C / 0.5C / 1C / 2C / 3C rate discharging tests, and 25℃ / 55℃ / 10℃ / 0℃ / -10℃ / -20℃ high and low temperature performance tests. The data are shown in Table 3.

[0156] Comparative Example 2

[0157] This comparative example provides a positive electrode material, and the preparation, characterization and performance testing methods are as follows:

[0158] (1) According to the molar ratio of nickel, iron and aluminum being 4:1:1, 61.795 g of spherical nickel hydroxide (Ni(OH)2), 34.974 g of ferrous acetate dihydrate (C4H6FeO4·2H2O), 8.497 g of lamellar aluminum oxide (Al2O3) and 40.635 g of lithium carbonate (Li2CO3) were weighed respectively; 7.679 g of glucose with a mass fraction of 5% was weighed (based on the sum of all raw materials);

[0159] (2) Place the weighed raw materials in a ball mill and use a planetary ball mill at 200 r / min for 30-60 min. Visually inspect the mixed powder material to see that the color is uniform and there is no graininess when grinding. Stop the ball milling and mixing.

[0160] (3) The mixed powder material is transferred into a sagger, spread evenly, and placed in a tubular atmosphere furnace. In a N2 atmosphere, the temperature is raised to 820°C at 2°C / min, kept at this temperature for 14 hours, and then cooled to 100°C at 4°C / min before being taken out;

[0161] (4) Ultracentrifugal grinding and screening of the cathode material cooled to room temperature are performed to obtain Li 1.1 Ni 2 / 3 Fe 1 / 6Al 1 / 6 O2 cobalt-free positive electrode material; weigh 20.00 g of the prepared positive electrode material sample, place it in a measuring cylinder, and use a tap density meter to test the tap density, wherein the vibration is 3000 times, and the frequency is 250 times / min;

[0162] (5) The prepared positive electrode material, conductive agent super carbon black (super-c65), binder (PVDF glue with a solid content of 6.25%) and NMP solvent were homogenized and coated to prepare a positive electrode sheet, wherein the mass fraction of the positive electrode material was 92%, the mass fractions of the conductive agent super carbon black (super-c65) and the binder were 4% each; graphite was used as the negative electrode, PP diaphragm was used, the electrolyte lithium salt was 1 mol / L LiPF6, and the solvent was EC and EMC with a mass ratio of 3:7, and assembled into a 2Ah soft-pack battery;

[0163] (6) Using the blue battery test system, the voltage range is 2.75-4.25V, the first charge and discharge test is carried out under 0.1C charge and 0.1C discharge. After two weeks of cycle, it is changed to 1C charge and 1C discharge. After 50 cycles, the charge and discharge cycle is carried out under 0.1C charge and 0.1C discharge for two weeks. The data is shown in Table 2;

[0164] (7) The blue battery test system was used with a voltage range of 2.75-4.25 V to conduct 0.33C / 0.5C / 1C / 2C rate charging and 0.33C / 0.5C / 1C / 2C / 3C rate discharging tests, and 25℃ / 55℃ / 10℃ / 0℃ / -10℃ / -20℃ high and low temperature performance tests. The data are shown in Table 3.

[0165] Figure 1 , Figure 2 This is a scanning electron microscope photograph of the positive electrode material of Example 1. It can be seen from the electron microscope photograph that the positive electrode material is composed of 200-600nm nano-scale spherical particle agglomerates and 1-10μm micron-scale single crystal particles stacked together, with a D50 particle size of about 1.5μm. There are many island-like coatings on the surface of the particles, and the coating is relatively dense and uniform, which is beneficial to reduce the occurrence of side reactions and improve material performance.

[0166] Figure 3 , Figure 4 This is a scanning electron microscope photograph of the positive electrode material of Example 2. It can be seen from the electron microscope photograph that the positive electrode material is composed of 200-500nm nano-scale spherical particle agglomerates and 1-8μm micron-scale single crystal particles stacked together, and the D50 particle size is about 1.3μm.

[0167] Figure 5 , Figure 6 This is a scanning electron microscope photograph of the positive electrode material of Example 3. It can be seen from the electron microscope photograph that the positive electrode material is composed of 300-500 nanometer-scale spherical particle agglomerates and 1-9μm micron-scale single crystal particles stacked together. The overall particles are mostly hard agglomerates, and the D50 particle size is about 1.5μm.

[0168] Figure 7 , Figure 8 This is a scanning electron microscope photograph of the positive electrode material of Example 4. It can be seen from the electron microscope photograph that the positive electrode material is composed of 200-600nm nano-scale spherical particle agglomerates and 1-10μm micron-scale single crystal particles stacked together, and the D50 particle size is about 2μm.

[0169] Fig. 9This is the first charge and discharge curve of the positive electrode material of Example 1. The first charge capacity, first discharge capacity and first efficiency of the material are 189.21 mAh / g, 98.41 mAh / g and 52.01%, respectively.

[0170] Fig.10 This is a 50-cycle capacity retention curve of the positive electrode material 1CC / 1DC of Example 1. The discharge capacity of the material under 1CC / 1DC cycle is 74.31 mAh / g, and the 50-cycle capacity retention rate is 48.99%.

[0171] Table 1 shows the Li / Me ratio (the ratio of the molar number of Li to the total molar number of all metal elements except Li) corresponding to Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 1 and Comparative Example 2, the molar fraction of each metal element except Li in all metal elements except Li, the doping elements and their mass fraction in the positive electrode material.

[0172] Table 1: Composition and tap density of positive electrode materials of Examples 1-5 and Comparative Examples 1-2

[0173]

[0174] Table 2 shows the first charge specific capacity, first discharge specific capacity, first efficiency, platform voltage, and 50-cycle capacity retention rate corresponding to Examples 1-5 and Comparative Examples 1-2.

[0175] Table 2: First charge specific capacity, first discharge specific capacity, first efficiency, platform voltage, and 50-cycle capacity retention rate of Examples 1-5 and Comparative Examples 1-2

[0176] Table 3 shows the cell rate charge, rate discharge and low temperature performance data corresponding to Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 1 and Comparative Example 2.

[0177] Table 3: Rate charge, rate discharge and low temperature performance data of Examples 1-5 and Comparative Examples 1-2

[0178]

Claims

1. A cobalt-free positive electrode material, characterized in that: The chemical formula of the cobalt-free positive electrode material is Li m Ni x Fe y Al z M (1-x-y-z) O2·nB2O3, wherein M is one or two selected from W element and Ti element, 1.05≤m≤1.2, 0.6≤x≤0.7, 0.1≤y≤0.2, 0.1≤z≤0.2, x+y+z<1, 0≤n≤0.005; in the cobalt-free positive electrode material, the mass content of M is 500ppm-100000ppm.

2. The cobalt-free positive electrode material according to claim 1, characterized in that In the cobalt-free positive electrode material, the mass content of M is 1000ppm-50000ppm.

3. The cobalt-free positive electrode material according to claim 1, characterized in that The M contains W elements.

4. The cobalt-free positive electrode material according to claim 3, characterized in that In the cobalt-free positive electrode material, the content of W element is 0.1-2wt%.

5. The cobalt-free positive electrode material according to claim 4, characterized in that In the cobalt-free positive electrode material, the content of W element is 0.2-1wt%.

6. The cobalt-free positive electrode material according to claim 5, characterized in that In the cobalt-free positive electrode material, the content of W element is 0.25-0.5wt%.

7. The cobalt-free positive electrode material according to claim 1, characterized in that The M includes a Ti element.

8. The cobalt-free positive electrode material according to claim 7, characterized in that In the cobalt-free positive electrode material, the content of Ti element is 0.1-2wt%.

9. The cobalt-free positive electrode material according to claim 8, characterized in that In the cobalt-free positive electrode material, the content of Ti element is 0.2-1wt%.

10. The cobalt-free positive electrode material according to claim 1, characterized in that: In the cobalt-free positive electrode material, the mass content of B element is 500-2000ppm.

11. The cobalt-free positive electrode material according to claim 1, characterized in that: The cobalt-free positive electrode material has one or more of the following characteristics: The cobalt-free positive electrode material is formed by stacking micron-sized single-crystal particles, and the micron-sized single-crystal particles are formed by agglomerating nano-sized spherical particles; The D50 particle size of the cobalt-free positive electrode material is 1-3 μm; The powder tap density of the cobalt-free positive electrode material is 1-2 g / cc.

12. The cobalt-free positive electrode material according to claim 11, characterized in that The particle size of the nano-scale spherical particles is 200-600nm.

13. The cobalt-free positive electrode material according to claim 11, characterized in that: The particle size of the micron-sized single-crystal-like particles is 1-10 μm.

14. A method for preparing the cobalt-free positive electrode material according to any one of claims 1 to 13, characterized in that: The method comprises the following steps: (1) mixing a lithium source, a nickel source, an iron source, an aluminum source, a carbon source and a M source uniformly; (2) heat-treating the mixture obtained in step (1) at 750-850° C. in an inert gas atmosphere to obtain a cobalt-free positive electrode material; Optionally, the method further comprises: (3) After the cobalt-free positive electrode material obtained in step (2) is uniformly mixed with a boron source, heat-insulating treatment is performed at 250-350° C. in an inert gas atmosphere to obtain a cobalt-free positive electrode material containing boron.

15. The method according to claim 14, characterized in that The method has one or more of the following features: The lithium source is selected from one or both of lithium carbonate and lithium hydroxide; The nickel source is selected from one or more of nickel hydroxide, nickel carbonate and nickel sulfate; The iron source is selected from one or more of ferrous acetate dihydrate, ferrous sulfate, ferrous carbonate, ferrous chloride and ferric chloride; The aluminum source is selected from one or both of aluminum oxide and aluminum hydroxide; The carbon source is selected from one or more of glucose, sucrose and graphene; The amount of the carbon source is 2-10% of the total mass of all raw materials; The M source includes one or two selected from tungsten trioxide and titanium dioxide; In step (1), the materials are mixed using a planetary ball mill; In step (2), a tubular atmosphere furnace is used for heat preservation; In step (2), the temperature is raised to the holding temperature at a heating rate of 1-3°C / min; In step (2), the holding time is 10-18 hours; In step (2), the temperature is lowered to below 100° C. after being kept warm; Step (2) further comprises grinding and screening the obtained cobalt-free positive electrode material; In step (3), the boron source is boric acid; In step (3), mixing is performed using a high-speed mixer; In step (3), a tubular atmosphere furnace is used for heat preservation; In step (3), the temperature is raised to the holding temperature at a heating rate of 1-3°C / min; In step (3), the holding time is 2-6 hours; In step (3), the temperature is lowered to below 100° C. after being kept warm.

16. The method according to claim 15, characterized in that The nickel source is spherical nickel hydroxide.

17. The method according to claim 15, characterized in that The aluminum source is selected from one or both of lamellar aluminum oxide and lamellar aluminum hydroxide.

18. The method according to claim 15, characterized in that Tungsten trioxide is nano-grade tungsten trioxide.

19. The method according to claim 15, characterized in that Titanium dioxide is nano-sized titanium dioxide.

20. The method of claim 15, wherein: In step (1), the rotation speed of the ball mill is 150-250 r / min.

21. The method of claim 15, wherein: In step (1), the ball milling time is 30-60 min.

22. The method of claim 15, wherein: In step (2), the cooling rate is 2-5°C / min.

23. The method of claim 15, wherein: In step (3), the rotation speed of the high-speed mixer is 1000-3000 r / min.

24. The method of claim 15, wherein: In step (3), the mixing time is 10-30 min.

25. The method of claim 15, wherein: In step (3), the cooling is natural cooling.

26. A positive electrode plate, characterized in that: The positive electrode sheet comprises the cobalt-free positive electrode material according to any one of claims 1 to 13.

27. A lithium ion battery or a lithium ion battery cell, characterized in that: The lithium-ion battery and lithium-ion battery cell include the positive electrode sheet as described in claim 26.

Citation Information

Patent Citations

  • Cobalt-free layered oxide cathodes

    US20200235390A1